MEMORIES OF JUDGMENT: CONSTRUCTING THE ICTY’S LEGACIES - Diane Orentlicher (Washington University Global Studies Law Review, 2020)
As the title of this symposium reflects, a critically important dimension of the Tribunal’s legacy is its role in understanding the war and genocide in Bosnia. In my remarks, I want to drill down on the word “understanding,” one of the most complex facets of the ICTY’s legacy. In brief, I will make four points. The first is that the ICTY’s expected contribution to understanding the 1990s conflict in Bosnia and the atrocities associated with that conflict was deeply important to many individuals whom I have interviewed in Bosnia-Herzegovina, as well as in Serbia, about the ICTY’s impact in their countries. Second, the hard facts and legal conclusions established through court procedures, however impartial and rigorous, do not automatically translate into general knowledge or understanding, particularly in polarized societies. On the contrary, despite the work of the ICTY, denialism about wartime atrocities has been on the rise in the former Yugoslavia. Third, the rise in denialism in Bosnia and its neighbors despite the ICTY’s work highlights a significant challenge for human rights champions everywhere, as well as for citizens of Bosnia, Serbia, and other Western Balkan countries. Finally, I will conclude with several thoughts about how we can honor the sacred duty of remembrance in a way that enriches our understanding of the past in the challenging context of polarized societies.
Keywords: War; genocide; ICTY